Antimicrobial resistance, virulence genes and biofilm formation in Enterococcus species isolated from milk of sheep and goat with subclinical mastitis - Mona A. El-Zamkan (Public Library of Science (PLoS), 2021)
This study is designed to discuss the antimicrobial resistance, virulence determinants and biofilm formation capacity of Enterococcus spp. isolated from milk of sheep and goat with subclinical mastitis in Qena, Egypt. The obtained isolates were identified by the VITEK2 system and 16S rDNA sequencing as E. faecalis, E. faecium, E. casseliflavus and E. hirae. Overall, E. faecalis and E. faecium were the dominant species recovered from mastitic milk samples. The antimicrobial susceptibility test evidenced multidrug resistance of the isolates against the following antimicrobials: oxacillin (89.2.%), followed by vancomycin (75.7%) and linezolid (70.3%). Also, most of these isolates (73%) could form biofilms. For example, 18.9% of Enterococcus strains formed strong biofilm, whereas 32.4% of isolates formed moderate biofilm and 21.6% of isolates formed weak biofilm. The most prevalent resistance genes found in our isolates were blaZ (54%), vanA (40%), ermB (51.4%), tetM (13.5%) and optrA (10.8%). Moreover, asa1 (37.8%), cylA (42.3%), gelE (78.4%), esp (32.4%), EF3314(48.6%) and ace (75.5%) were the most common virulence genes. A significant correlation was found between biofilm formation, multidrug resistance and virulence genes of the isolates. This study highlights several aspects of virulence and harmfulness of Enterococcus strains isolated from subclinical mastitic milk, which necessitates continuous inspection and monitoring of dairy animals.